Effect of computer aided teaching of acid-base subject on the attitude towards science and technology class - BAYRAM, HALE (ELSEVIER SCIENCE BV, 2010)
In this study, the effect of computer aided teaching of acid-base subject on the attitude towards science and technology course is investigated. In the material developed by the researcher, it was aimed to enable students learn acid-base subject by interactive animations and simulations. For the purpose of collecting data in the research, Attitude towards Science and Technology Course Scale, developed by Nuhoglu (2008), was used. In the statistical analysis of data, t-test was performed. Results indicate that, teaching of acid-base subject supported with computer aided teaching had a positive effect on the attitude of students towards science and technology course. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Acid-base; computer aided teaching; science and technolojy; attitude scale; INSTRUCTION